2011
DOI: 10.1371/journal.pone.0020239
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Subsidies on the Ecological Sustainability and Future Profits from North Sea Fisheries

Abstract: BackgroundThis study examines the impact of subsidies on the profitability and ecological stability of the North Sea fisheries over the past 20 years. It shows the negative impact that subsidies can have on both the biomass of important fish species and the possible profit from fisheries. The study includes subsidies in an ecosystem model of the North Sea and examines the possible effects of eliminating fishery subsidies.Methodology/Principal FindingsHindcast analysis between 1991 and 2003 indicates that subsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Another example from the North Sea (Heymans et al 2011) indicates the possible trade-offs between a future focused on maximizing the profitability of fisheries vs. a future pursuing a vision of a more "resilient" ecosystem with more long-lived species. The study found that a totally different fleet structure would be needed to achieve these scenarios and that there would be major effects on the overall redundancy in the ecosystem.…”
Section: Scenarios Learning and Resiliencementioning
confidence: 99%
“…Another example from the North Sea (Heymans et al 2011) indicates the possible trade-offs between a future focused on maximizing the profitability of fisheries vs. a future pursuing a vision of a more "resilient" ecosystem with more long-lived species. The study found that a totally different fleet structure would be needed to achieve these scenarios and that there would be major effects on the overall redundancy in the ecosystem.…”
Section: Scenarios Learning and Resiliencementioning
confidence: 99%
“…The structure of the model and data sources used to parameterize the food web in 1991 are described in detail in Mackinson and Daskalov (2007) and summarized in Heymans et al (2011). Substantive updates used in defining a Key Run 1 were published in detail in ICES (2011).…”
Section: The Ecosystem Modelmentioning
confidence: 99%
“…34 B SEA EwE Polovina 1984;Christensen & Pauly, 1992;Christensen & Walters, 2004;Walters and Martell 2004;Walters and Christensen 2007;Walters et al, 1997Walters et al, , 1999Walters et al, , 2000Tomczak et al, 2012Tomczak et al, , 2013. Polovina 1984;Christensen & Pauly, 1992;Christensen & Walters, 2004;Walters and Martell 2004;Walters and Christensen 2007;Walters et al, 1997Walters et al, , 1999Walters et al, , 2000Plagányi and Butterworth 2004;Mackinson, 2014;Mackinson & Daskalov, 2007;Mackinson, Deas, Beveridge, & Casey, 2009;Heymans, Mackinson, Sumaila, Dyck, & Little, 2011;ICES 2011;Romagnoni et al, 2015;Colléter et al, 2015. T A B L E 2 (Continued)…”
mentioning
confidence: 99%